PENINGKATAN PENILAIAN RISIKO OLEH RISK-BASED INTERNAL AUDITING MELALUI AGILE AUDIT PLANNING PADA ERA NEW NORMAL - Wicaksono Bagus Dewandaru; Ranti Widiastuti; Zahra Wanda (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2020)
Every business organization is currently faced with various large-scale business risks caused by the COVID-19 pandemic and government policies that limit the company's business flow. The business flow from upstream to downstream is disrupted due to the pandemic that occurs and the transition during the new normal period which affects organizational performance, for example, MSMEs. The role of internal auditing is very necessary to ensure that operational performance continues to run effectively and optimally under the uncertainty of the new normal era. Accountants as internal auditors with the concept of risk-based internal auditing must respond and quickly mitigate various risks that may occur as an effort to assist management. The concept of agile portfolio management, namely agile audit planning, is considered relevant in this condition, agile approach is widely studied as a solution in improving internal audit performance. Agile audit planning is considered to be more flexible and effective than traditional audit procedures. This paper provides a solution in increasing risk assessment for internal auditors in the form of risk assessment to mitigate the risks in business uncertainty due to pandemics, which is implemented in local MSME with the aim of assisting in assessing business risks. This paper was prepared using a qualitative descriptive method, with secondary reference sources through literature review from related literature sources and primary by interview method. The result of this paper is an idea of the effectiveness of agile audit planning in assessing the risks obtained from comparative analysis with traditional audit procedures and analysis of the benefits of implementing agile audit planning in MSMEs. This paper will provide an overview of the advantages of implementing agile audit planning in the new normal.Keywords: Agile Audit Planning, Internal Audit, MSME, New Normal, Risk-Based Internal Auditing